Enhancement of Photoelectrochemical Performance in Water Oxidation over Bismuth Vanadate Photoanodes by Incorporation with Reduced Graphene Oxide. Issue 18 (29th July 2015) - Hu, Yingfei; Su, Yao; Huang, Huiting; Qian, Qinfeng; Guan, Zhongjie; Feng, Jianyong; Li, Zhaosheng; Zou, Zhigang
Abstract Bismuth vanadate photoanodes often suffer from poor electron transport, which restricts their photoelectrochemical performance in water oxidation. Here, reduced graphene oxide sheets with excellent electronic conductivity are introduced to bismuth vanadate photoanode films to provide a channel for electron transport. As a result, the charge separation efficiency of the photoanode films increases from 59 to 78 % at 420 nm and 1.23 V (vs. the reversible hydrogen electrode) under back irradiation. In particular, the onset potential for photoelectrochemical water oxidation over reduced graphene oxide–bismuth vanadate photoanode films has a cathodic shift of approximately 120 mV in potassium borate electrolyte compared to bare bismuth vanadate photoanode films.